Estimating the Implicit Inflation Target of the South African Reserve Bank - Klein, Nir (IMF Working Papers; Working Paper ;, 2012)
This paper applies a state-space approach to estimate the implicit inflation target of the South African Reserve Bank (SARB) since the adoption of the Inflation Targeting (IT) framework. The paper's findings are two. First, although the official inflation target range is 3.6 percent, in practice, the SARB seems to have aimed for the upper segment of the band (41.2 .6 percent) for most of the period, despite the substantial variation of the output gap. Second, the estimation results show that the implicit inflation target varied over time, and in recent years it has shifted toward the upper limit of the inflation target range. This perhaps suggests that since the outbreak of the financial crisis in 2008, the SARB's tolerance for higher inflation has somewhat increased to better support economic activity.